Public Space Behaviors and Intentions: The Role of Gender through the Window of Culture, Case of Kerman - Jalalkamali, Aida; Doratli, Naciye (Mdpi, 2022)
Urban public spaces are the spatial nexus of social interactions, activities, and expressions. Society manifests itself within these spaces through different lenses such as cultures and norms. The framework and restrictions related to gender-based behavior play a central role in the discourse about inclusivity and equity in urban public spaces when viewed through these lenses. There is, however, a gap in the literature that addresses how culture and gender influence public space behaviors and intentions within a traditional and modern cultural framework. The current study tests whether culture correlates with public space behavior on a neighborhood scale. A comparative study was conducted between two distinct neighborhoods in the city of Kerman, Iran. The two cases were selected due to their significant differences in how women use and interact with urban space. The effects of gender differences and perceived constraints on how residents manifest their behavior in public spaces were investigated. The study further investigated whether gender has a significant relationship with the level of appropriateness of certain public space behaviors and the intention to pursue them. The findings indicate significant cultural differences in both behavioral practice and behavioral intentions among the respondents. Furthermore, in traditional neighborhoods, the findings support significant gender-dependent differences in public space behavior, even though this gap is not apparent regarding intentions toward public space behaviors. The findings show a significantly greater disparity between traditional and modern districts in women's perceived behavioral restrictions on personal expression.
Keywords: gender; culture; public space behavior; Iran; traditional ideology